2018
DOI: 10.1186/s12958-018-0419-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the prevalence of hyperuricemia and reproductive hormones in polycystic ovary syndrome

Abstract: BackgroundThe prevalecne of hyperuricemia in polycystic ovary syndrome (PCOS) is still uncertain. We aimed to investigate the prevalence of hyperuricemia in PCOS and to determine the influence of reproductive hormones on uric acid concentration.MethodsThis retrospective cross-sectional study was performed at a large reproductive medicine center. Between March 2007 and October 2016, a total of 1,183 women with PCOS and 10,772 women without PCOS were included. PCOS was diagnosed according to the Rotterdam criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 35 publications
6
42
0
3
Order By: Relevance
“…Previous studies have shown increasing SUA levels were positively associated with increased cardiovascular mortality and increased the risk of adverse pregnancy outcomes in PCOS patients, therefore SUA level determination is valuable for women with PCOS [15,25]. Several studies had reported that the SUA levels and prevalence of hyperuricemia increased greatly in obese PCOS women [13], which was similar to present results. However, the underlying mechanism had not been clear until now, there were some hypotheses as following: body fat accelerated SUA production and the synthesis of triglyceride [26] and hyperinsulinemia could decrease renal UA excretion [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown increasing SUA levels were positively associated with increased cardiovascular mortality and increased the risk of adverse pregnancy outcomes in PCOS patients, therefore SUA level determination is valuable for women with PCOS [15,25]. Several studies had reported that the SUA levels and prevalence of hyperuricemia increased greatly in obese PCOS women [13], which was similar to present results. However, the underlying mechanism had not been clear until now, there were some hypotheses as following: body fat accelerated SUA production and the synthesis of triglyceride [26] and hyperinsulinemia could decrease renal UA excretion [27].…”
Section: Discussionsupporting
confidence: 90%
“…Hyperuricemia is a disease of impaired uric acid metabolism. A recent study indicated that the prevalence of hyperuricemia in PCOS women is more than 25%, while 58.75% of obese PCOS women approximately suffer from hyperuricemia, which was almost three folds higher than that in PCOS women with normal BMI [13]. Elevated SUA level not only increased the risk of gout, but also increased cardiovascular risk by promoting in ammation, oxidative stress and proliferation in PCOS women [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown increasing SUA levels were positively associated with increased cardiovascular mortality and increased the risk of adverse pregnancy outcomes in PCOS patients, therefore SUA level determination is valuable for women with PCOS [15,25]. Several studies had reported that the SUA levels and prevalence of hyperuricemia increased greatly in obese PCOS women [13], which was similar to our results. However, the underlying mechanism had not been clear until now, there were some hypotheses as following: body fat accelerated SUA production and the synthesis of triglyceride [26] and hyperinsulinemia could decrease renal UA excretion [27].…”
Section: Discussionsupporting
confidence: 90%
“…Hyperuricemia is a disease of impaired uric acid metabolism. A recent study indicated that the prevalence of hyperuricemia in PCOS women is more than 25%, while 58.75% of obese PCOS women approximately suffer from hyperuricemia, which was almost three folds higher than that in PCOS women with normal BMI [13]. Elevated SUA level not only increased the risk of gout, but also increased cardiovascular risk by promoting in ammation, oxidative stress and proliferation in PCOS women [14].…”
Section: Introductionmentioning
confidence: 99%
“…Urate is the product of purine metabolism and is mainly produced in the liver. Clinical studies have shown that urate is related to many hormones in the body, including luteinizing hormone (LH), follicle-stimulating hormone (FSH), estrogen(E 2 ), and thyroid hormone (TH) ( Mumford et al, 2013 ; Mu et al, 2018 ). Thus far, there have been conflicting reports concerning the relationship between thyroid hormone and serum urate.…”
Section: Introductionmentioning
confidence: 99%